Technology-Infused Project-Based Language Learning: A Conceptual Framework for Academic Writing Instruction - Sri Wahyuni; Nur Hidayanto Pancoro Setyo Putro; Asnawi Asnawi; Putri Asilestari; Anwar Efendi (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2026)
For Generation Z learners, academic writing presents a paradox in higher education. While it offers valuable benefits, it also poses notable challenges (e.g., limited development of critical thinking skills, insufficient academic literacy, and a lack of familiarity with scientific writing conventions). In response to this paradox, project-based language learning (PBLL) and learning technologies offer innovative avenues to improve students’ writing products and processes. This article aims to develop and articulate the Technology-Infused Project-Based Language Learning (TIPBLL) model as a conceptual framework for academic writing instruction. Methodologically, this article employs a qualitative conceptual analysis through a structured synthesis of literature on PBLL, technology-enhanced language learning, academic writing pedagogy, and digital technology integration, particularly artificial intelligence. The TIPBLL model integrates PBLL principles, digital technology infusion, and academic writing pedagogy into a unified framework. This article analyses significant learning theories and pedagogical perspectives, including sociocultural theory, the Zone of Proximal Development (ZPD), the dual focus of writing (form and function), and PBLL within the PLATE framework. The findings of the conceptual synthesis highlight conceptual deficiencies in the literature, particularly the tendency to treat projects, technology, and writing as separate components. TIPBLL is then introduced as a learning model that positions technology as an integral component embedded across the stages of project-based academic writing. The article also discusses TIPBLL’s future directions for research and pedagogical practice. Overall, TIPBLL offers a potential framework for building academic writing instruction that is more authentic, collaborative, reflective, and aligned with the demands of 21st-century digital literacy.